The Role of Employee Retention as Mediation on the Influence of Organizational Culture and Workload on Employee Engagement - Indra Setiawan; Sri Hastuti (Privietlab, 2022)
Seeing the competition in the business world today is also increasingly competitive and the role of an employee in the survival of a company or organization is so important because however sophisticated the technology is used without being supported by the presence of humans as implementers in its operational activities, as a result, it will not be able to produce output that is in accordance with what is expected. , which is where goods or services should be issued by the company according to the standard SOP they have. The purpose of this study was to determine the analysis of employee engagement level factors mediated by employee retention at the K-55 Guards Security Service company. The sampling method used random sampling method with a sample of 171 employees. The type of research used is quantitative. For data collection includes observation, questionnaires and literature study. Data processing analysis was carried out using PLS (Partial Least Square) analysis technique through SmartPLS version 3.0 software. Based on the results of this study, it can be concluded that organizational culture has a positive and significant effect on employee retention. Workload has a positive and significant effect on employee retention in employees. Organizational culture has a positive and significant impact on employee engagement. Employee retention can mediate between organizational culture and employee engagement. Workload has a positive and significant effect on employee engagement on employees. Employee retention has a positive and significant effect on employee engagement on employees. Employee retention can mediate between workload and employee engagement.